THE FINANCIAL ASPECTS OF DEPRECIATION ACCOUNTING. - Mason, Perry (The Accounting Review, 1935)
Abstract The problems of depreciation accounting are limited to the periodic determination of costs and expenses and to the amortization of the corresponding asset accounts, but the financial aspects of depreciation accounting present some important problems, and various misconceptions of the actual effects and relationships are widespread. The recording of depreciation as such has no effect upon the amount of assets which come into the business except that in so far as the selling price of a product may be based upon its cost of production, depreciation, as one of the costs of production may be said to help determine the gross income. The financial aspects of depreciation accounting may be utilized in the administration of the financial budget. The amount of depreciation included in the budget of expenses may ordinarily be considered as available funds in the financial budget and may be appropriated for any purpose. If it is feasible or desirable to make replacements with borrowed capital, the funds made available by the depreciation accounting might well be used to retire the original indebtedness or other original investment.